Mediating effect of psychological empowerment on relationships between organizational climate, culture and commitment of lecturers in Borno State, Nigeria (abstract tidak lengkap) - Abba Aji, Abubakar (2017)
Previous studies on Organizational commitment argues for employees personal characteristic, job characteristic and work experience, as the determinants of commitment in the organization. Rarely do studies examine contextual factors such as organizational cultures and organizational climate as factors responsible for organizational commitment, as well as mediating effect of psychological empowerment on these relationships, particularly among Higher Education Institutions (HEIs) employees. Therefore, this study aims to determine the mediating effect of psychological empowerment on the relationship between organizational climate, organizational culture and organizational commitment among HEIs lecturers in Borno State, Nigeria. This study employed descriptive survey method, using validated self-administered questionnaires. A total of 417 questionnaires were distributed using Cochran formulae for sample size determination. However, 325 valid responses were returned representing 79 percent. The collected data were analyzed with descriptive statistical tools such as percentage, mean and standard deviation, to describe the respondents’ characteristics and the levels of all the variables in the study. The descriptive analysis revealed that the level of all the tested variables examined in this study were moderate with composite mean scores. Eight (8) research hypotheses were formulated and tested using inferential statistical tools such as independent sample t-test, Pearson correlation, and Structural Equation Modeling (SEM). SEM analysis was also employed to test and establish existence of convergent validity and discriminant validity of the measures. The measurement model confirmed the appropriateness of the measured data